Experimental Study on the Unsteady Characteristics and the Impact Performance of a High-Pressure Submerged Cavitation Jet - Yongfei Yang; Wei Li; Weidong Shi; Ling Zhou; Wenquan Zhang (Shock and Vibration)
High-pressure submerged cavitation jet is widely used in the fields of material peening, petroleum drilling, and ocean engineering. The impact performance of the jet with intensive cavitation is related to the factors such as working condition and the nozzle geometry. To reveal the relationship between the nozzle divergent angle and the jet pressure on the unsteady characteristics of the jet, high-speed photography with frame rate of 20000 fps is used to record the image of the cavitation clouds. Grayscale analysis algorithm developed in MATLAB is used to study the effects of injecting condition on the special structure, unsteady characteristics, and shedding frequency of the cavitation bubbles. The impact load characteristics of the cavitation jet with different cavitation numbers and stand-off distances are recorded using a high-response pressure transducer. It is found that the cavitation number is the main factor affecting the cavitation morphology of the submerged jet. The lower the cavitation number is, the more intense the cavitation occurs. The outlet divergent angle of the convergent-divergent nozzle also has a significant influence on the development of the cavitation clouds. In the three nozzles with the outlet divergent angles of 40°, 80°, and 120°, the highest bubble concentration is formed usinga nozzle with a divergent angle of 40°, but the high-concentration cavitating bubbles are only distributed in a very small range of the nozzle outlet. The cavities generated by using the nozzle with a divergent angle of 80° can achieve good results in terms of concentration and distribution range, while the nozzle with divergent angle of 120° has lower cavitation performance due to the lack of the constraint at the outlet which intensifies the shear stress of the jet. According to the result of frame difference method (FDM) analysis, the jet cavitation is mainly formed in the vortex structure generated by the shearing layer at the nozzle exit, and the most severe region in the collapse stage is the rear end of the downstream segment after the bubble cloud sheds off. The impact load of the cavitation jet is mainly affected by the stand-off distance of the nozzle from the impinged target, while the nozzle outlet geometry also has an effect on the impact performance. Optimizing the stand-off distance and the outlet geometry of the nozzles is found to be a good way to improve the performance of the cavitation jet.